Evaluating the need for standardised disease manifestation categories in patients infected with the tick-borne encephalitis virus: A Delphi panel - Kate Halsby; Gerhard Dobler; Ava Easton; Guntis Karelis; Lenka Krbková; Jan Kyncl; Johann Sellner; Franc Strle; Malin Veje; Joanna Zajkowska; Dace Zavadska; Frederick J. Angulo; et al. (Ticks and Tick-Borne Diseases)
Categorization systems for tick-borne encephalitis virus (TBEV) infection lack consistency in classifying disease severity. To evaluate the need for a standard, consensus-based categorisation system for TBEV infection across subtypes, we gathered an expert panel of clinicians and scientists with diverse expertise in TBEV infection. Consensus was sought using the Delphi technique, which consisted of 2 web-based survey questionnaires and a final, virtual, consensus-building exercise. Ten panellists representing 8 European countries participated in the Delphi exercise, with specialities in neurology, infectious disease, paediatrics, immunology, virology, and epidemiology. Panellists reached unanimous consensus on the need for a standardised, international categorisation system to capture both clinical presentation and severity of TBEV infection. Ideally, such a system should be feasible for use at bedside, be clear and easy to understand, and capture both the acute and follow-up phases of TBEV infection. Areas requiring further discussion were (1) the timepoints at which assessments should be made and (2) whether there should be a separate system for children. This Delphi panel study found that a critical gap persists in the absence of a feasible and practical classification system for TBEV infection. Specifically, the findings of our Delphi exercise highlight the need for the development of a user-friendly classification system that captures the acute and follow-up (i.e., outcome) phases of TBEV infection and optimally reflects both clinical presentation and severity. Development of a clinical categorisation system will enhance patient care and foster comparability among studies, thereby supporting treatment development, refining vaccine strategies, and fortifying public health surveillance.